Enantioselective α-Boryl Carbene Transformations - Huang, Ming-Yao; Zhu, Shou-Fei (Synlett, 2024)
α-Boryl carbenes, which are hybrid structures combining elements of carbenes and boryl groups, represent promising intermediates for constructing organoboron compounds. However, these carbenes are challenging to synthesize and exhibit limited structural diversity. Moreover, their applications in asymmetric transformations remain largely unexplored. In this study, we utilized boryl cyclopropenes as precursors to rapidly synthesize α-Bpin metal carbenes, a novel category of intermediates critical for the synthesis of chiral organoboron molecules. Facilitated by a copper complex modified by a chiral bisoxazoline ligand, these α-boryl carbenes participate in a range of highly enantioselective transfer reactions, including B–H and Si–H insertions, as well as cyclopropanation and cyclopropanation/Cope rearrangement processes. This methodology provides access to previously inaccessible, yet highly useful, chiral organoborons, thereby significantly advancing both carbene and organoboron chemistry.1 Introduction2 Previous Discovery and Our Design3 Copper Catalyzed Enantioselective α-Boryl Carbene Transfer Reactions4 Mechanistic Studies5 Conclusions
Keywords: α-boryl carbenes; asymmetric catalysis; cyclopropenes; carbene transfer reactions; chiral organoborons